Pola Pengobatan Gejala pada Tatalaksana Pasien Lansia Covid-19 dengan Komorbid Diabetes Melitus di RSUP Dr. M. Djamil Padang Tahun 2020 - Dessy Abdullah; Zahra Aufi Adzkia; Khomeini; Irwan Triyansyah; Yuliza Birman (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2022)
COVID-19 is a respiratory disease caused by SARS-CoV-2. This disease more easily attacks ederly patienrs or patients with certain comorbidities. One of the most common comorbidities found is diabetes mellitus. Until now there is no definitive treatment for COVID-19. This study aims to determine the symtomps medication pattern in the treatment of COVID-19 of ederly COVID-19 patients with comorbid diabetes mellitus at RSUP Dr. M. Djamil Padang in 2020. The type of research used is categorical descriptive. The sampling technique used was purposive sampling technique. Sample obtained 40 samples. The Results of this study indicate that the most age categories in elderly COVID-19 patients with comorbid diabetes mellitus are 60-69 years, as many as 36 respondents (87.5%), the most gender is male, namely 31 respondents (78%), the degree of symptoms The most clinical patients with mild symptoms were 15 respondents (38%), the most common cough medicine used for the treatment of cough symptoms was mucolytic, as many as 36 respondents (90%), treatment of sore throat symptoms used was corticosteroids given to 20 respondents ( 50%) and no corticosteroids were given to 20 respondents (50%), and the drug most frequently used for the treatment of headache or fever symptoms was paracetamol, which was 29 respondents (73%). The most frequently used treatment patterns for elderly COVID-19 patients with comorbid diabetes mellitus are mucolytic cough medicine, corticosteroids and paracetamol.